Curriculum Changes from an Educational Sociology Perspective - Lestari, Liza Puji; Idi, Abdullah; Karoma, Karoma (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This article discusses curriculum changes in Indonesia from the perspective of educational sociology, focusing on the implementation of the 2013 Curriculum and the Merdeka Belajar-Kampus Merdeka (MBKM) policy. Using a qualitative approach through literature review, this research examines how the curriculum functions as a social instrument influenced by and influencing various social factors. The 2013 Curriculum emphasizes competency-based learning aimed at developing critical and creative skills, while MBKM provides students with opportunities to engage in practical learning experiences outside the classroom. The findings indicate that curriculum changes have significantly impacted social interactions within educational settings, enhancing student engagement and building more adaptive individual character. However, challenges such as infrastructure gaps and educator readiness persist in its implementation. This study suggests stronger collaboration between the government, educational institutions, and society to address these challenges and achieve inclusive and relevant educational goals.